Fabrication of Surface-Porous Metallic Coatings by Cold Spray Additive Manufacturing and Their Applications in Heat Transfer - Chen, Yan (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2026)
This dissertation presents a systematic investigation into the formation mechanisms of surface open pore structures in cold spray solid state additive manufacturing and their functional application in boiling heat transfer enhancement. The objective is to establish an integrated research framework that spans from structural formation mechanisms to engineering performance validation. In response to the limitations of conventional porous heat transfer surfaces in terms of structural controllability, fabrication cost, and scalability, this work proposes a design pathway based on deposition non-uniformity in cold spray processing to enable both formation and controllable construction of surface open pore architectures. Under identical cold spray processing conditions, a comparative study was conducted on Al, Cu, and Ti-6Al-4V (Ti64). The results demonstrate that only Ti64 spontaneously forms a honeycomb like surface open pore network during deposition. Cross sectional observations and three dimensional micro computed tomography reconstruction reveal that this structure originates from spatially selective bonding during the initial deposition stage. Owing to the high critical deposition velocity and intrinsic strength of Ti64, particle velocity dispersion leads to pronounced deposition non-uniformity. This non-uniformity is continuously inherited and amplified during multilayer accumulation, ultimately forming through thickness open channels and wall like skeletal structures. On this basis, pool boiling heat transfer was employed as a performance evaluation platform to systematically investigate the functional behavior of cold sprayed porous Ti64 surfaces. Experimental results show that such surfaces significantly reduce nucleation superheat and enhance critical heat flux. The enhancement mechanism can be attributed to two primary effects. First, the cavity structures provide abundant and stable nucleation sites that promote early bubble generation. Second, the wall like skeleton acts as a geometric barrier to suppress lateral bubble coalescence, thereby delaying dry spot propagation and hydrodynamic instability. It was also observed that as coating thickness increases, the relatively low thermal conductivity of Ti64 introduces additional thermal resistance, partially diminishing the structural enhancement effect. This finding indicates a pronounced coupling between structural functionality and intrinsic thermophysical properties, highlighting the necessity of balancing pore structure enhancement and conductive heat transfer pathways in optimized design. To further achieve structural designability and material transferability, a substrate pre-treatment driven geometric regulation strategy was proposed. By pre-fabricating pore arrays and related structures on aluminum substrates, low deposition efficiency regions were intentionally introduced to guide the formation of controllable open pore networks during subsequent cold spray deposition. Through orthogonal experimental design and response surface analysis, the influences of pore diameter, pore spacing, and coating layer number on critical heat flux were systematically evaluated, establishing quantitative correlations among geometric parameters, structural morphology, and heat transfer performance. The results indicate that pore diameter and pore spacing are the dominant parameters, and appropriate matching can significantly enhance heat transfer performance while maintaining manufacturability. Overall, this dissertation systematically elucidates the formation mechanisms and functional enhancement principles of cold spray induced surface open pore structures and establishes the intrinsic relationship among deposition behavior, structural evolution, and heat transfer performance. The findings provide both theoretical foundations and practical engineering pathways for the design and scalable fabrication of efficient boiling heat transfer surfaces with multiscale architectures and material adaptability.
APPROVED